فعالية تعليم الترجمة الفورية من الإندونيسية إلى العربية في ترقية مهارة الكلام: The Effectiveness of Teaching Simultaneous Translation from Indonesian into Arabic in Improving Students' Speaking Skills - Olivia Ananda Fitrah; Rusydi Baya’gub; Ali Muhsin (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
Simultaneous translation learning is a learning method by translating the source language into the target language directly, both in spoken and written form. For example translating Arabic into Indonesian. Studying this translation method, students are able to broaden their knowledge, be able to master foreign languages ​​and have the ability to translate them. In addition, students can easily, without hesitation, and dare to say words or speak Arabic to their teachers, friends and the people around them. So accustomed to speaking Arabic in everyday life without fear of being wrong. This research approach is quantitative, while this type of research is descriptive quantitative. The population in this study were 127 students of Arabic language education semester VI Batch 19, while the sample taken from some classes was 38 students. The techniques used to collect data in this study include: observation, interviews, questionnaires, and documentation. Then the data analysis technique uses quantitative descriptive statistics, validity test, reliability test, normality test, homogeneity test, simple linear regression analysis test, coefficient of determination test and t test. Conclusion This study is based on test results, the coefficient of determination (R Square) = 0.533 or 53.3%. This means that the translation fauriyah learning variable from Indonesian to Arabic (x) affects the speaking skill variable (y) = 53.3%. While the rest (100% - 53.3% = 46.7%) is influenced by other variables, namely variables that are not examined. Thus the value of the coefficient or calculation of r is 0.533 greater than the value of r table, which means the null hypothesis (Ho) is rejected and (Ha) is accepted. Meanwhile, based on the results of the midterm and final semester exams, around 80% students experienced an increase. The average student scores 88. So each student experiences an increase of 11%